Alterations in DNA methylation associate with fatty liver and metabolic abnormalities in a multi-ethnic cohort of pre-teenage children. Issue 11 (2nd November 2022) - Moylan, Cynthia A.; Mavis, Alisha M.; Jima, Dereje; Maguire, Rachel; Bashir, Mustafa; Hyun, Jeongeun; Cabezas, Melanie N.; Parish, Alice; Niedzwiecki, Donna; Diehl, Anna Mae; Murphy, Susan K.; Abdelmalek, Manal F.; et al.
ABSTRACT: Non-Alcoholic fatty liver disease (NAFLD) is the leading cause of chronic liver disease in children. Epigenetic alterations, such as through DNA methylation (DNAm), may link adverse childhood exposures and fatty liver and provide non-invasive methods for identifying children at high risk for NAFLD and associated metabolic dysfunction. We investigated the association between differential DNAm and liver fat content (LFC) and liver injury in pre-adolescent children. Leveraging data from the Newborn Epigenetics Study (NEST), we enrolled 90    mother-child dyads and used linear regression to identify CpG sites and differentially methylated regions (DMRs) in peripheral blood associated with LFC and alanine aminotransferase (ALT) levels in 7–12yo children. DNAm was measured using Infinium HumanMethylationEPIC BeadChips (Illumina). LFC and fibrosis were quantified by magnetic resonance imaging proton density fat fraction and elastography. Median LFC was 1.4% (range, 0.3–13.4%) and MRE was 2.5 kPa (range, 1.5–3.6kPa). Three children had LFC ≥ 5%, while six (7.6%) met our definition of NAFLD (LFC ≥ 3.7%). All children with NAFLD were obese and five were Black. LFC was associated with 88 DMRs and 106 CpGs (FDR<5%). The top two CpGs, cg25474373 and cg07264203, mapped to or near RFTN2 and PRICKLE2 genes. These two CpG sites were also significantly associated with a NAFLD diagnosis. As higher LFC associates with an adverse cardiometabolic profile already in childhood, altered DNAm may identify these children early in disease course for targeted intervention. Larger, longitudinal studies are needed to validate these findings and determine mechanistic relevance.